Trends in Alcohol's Harms to Others (AHTO) and Co-occurrence of Family-Related AHTO: The Four US National Alcohol Surveys, 2000-2015 - Thomas K. Greenfield; Katherine J. Karriker-Jaffe; Lauren M. Kaplan; William C. Kerr; Sharon C. Wilsnack (SAGE Publishing, 2015)
Various harms from others' drinking have been studied individually and at single points in time. We conducted a US population 15-year trend analysis and extend prior research by studying associations of depression with combinations of four harms - family/marriage difficulties, financial troubles, assault, and vandalism - attributed to partners or family members. Data come from four National Alcohol Surveys conducted by telephone in 2000, 2005, 2010, and 2015 (analytic sample = 21,184). Weighted logistic regression models estimated time trends adjusting for victim characteristics (gender, age, race/ethnicity, marital status, poverty, employment, family history of alcohol problems, and drinking maximum). The 2015 survey asked the source of the harm; we used similar models to examine characteristics, including anxiety and depression, associated with various combinations of family/marriage, financial, and assault harms due to partner's/spouse's/family members' drinking. A significant upward trend ( P < 0.001) from 2000 to 2015 was seen for financial troubles but not for other harms due to someone else's drinking. In 2015, depression and/or anxiety were strongly associated with exposures to harms and combinations of harms identified as stemming from drinking spouse/partner and/or family members. The results shed new light on 15-year trends and associations of harms with personal characteristics. A replicated finding is how the victim's own heavy drinking pattern is implicated in risks for exposures to harms from someone else's drinking. Documenting risk factors for and mental health impacts is important for interventions to reduce alcohol's harm to others.